PENAFSIRAN PASAL 156 KUHP TERHADAP PENGHINAAN ATAS SUATU DAERAH DALAM KASUS TEMPAT JIN BUANG ANAK - Erdianto Effendi; Tri Novita Sari Manihuruk (Jurnal Restorative Justice, 2022)
Insult to an area in the case of "where the genie throws children" is interpreted by Article 156 of the Criminal Code. Looking at the facts of the case, it can be seen that it is true that the expression "jinn throws away children" is a derogatory idiom or expression, but the object in that expression is a certain place or area or region, not the group of people who are there. As for the object referred to in Article 156 which becomes the object of the offense is a person or ethnicity, ethnicity or population group. The research method used is normative research. The results of the study show that in the case of the statement where the genie disposes of the child, even though the words are demeaning, the statement cannot be applied as an offense against a tribe, race or class, because the statement is addressed to a region or region not to a particular community. However, it is possible to apply Article 14 paragraph (2) or Article 15 of Law Number 1 Year 1946.